Survey of metallo-β-lactamase-producing Enterobacteriaceae colonizing patients in European ICUs and rehabilitation units, 2008–11. (10th March 2015) - Papagiannitsis, C. C.; Izdebski, R.; Baraniak, A.; Fiett, J.; Herda, M.; Hrabák, J.; Derde, L. P. G.; Bonten, M. J. M.; Carmeli, Y.; Goossens, H.; Hryniewicz, W.; Brun-Buisson, C.; et al.
Abstract: Objectives: The objective of this study was to perform a multinational survey of patients' colonization by metallo-β-lactamase (MBL)-producing Enterobacteriaceae, including their molecular characterization. Methods: Patients in 18 hospital units across Europe and Israel ( n  = 17 945) were screened between mid-2008 and mid-2011. MBL-producing isolates were typed by PFGE and MLST. MBL genes were amplified and sequenced within their integrons. Plasmids with MBL genes were analysed by nuclease S1 plus hybridization profiling, mating and transformation assays, and by PCR-based replicon typing. Results: Ninety-one patients in nine centres (six countries), including 62 patients in two Greek ICUs, carried 94 non-duplicate MBL-producing organisms. Klebsiella pneumoniae isolates from Greece dominated ( n  = 57) and belonged mainly to ST147, ST36 and ST383. All but one of the isolates expressed VIM-1-type MBLs. Isolates of Greek origins produced five enzymes, including new VIM-39, encoded by class 1 integrons of four types. In-e541-like elements prevailed, comprising six variants located on IncR, IncFIIK, IncR + FIIK, IncR + A/C or non-typeable plasmids. The other group were new In4873 and In4863, being the first In416-like elements identified in Greece, which were present on IncA/C or non-typeable plasmids. Isolates from other countries produced only VIM-1 and the major integron was In916, identified in 16 organisms from France, Italy and Spain. In916 was carried by four plasmid types, including IncA/C, IncFIIK and IncHI2. Other integrons included a new element, In3103, in Spain and In110 identified only in Latvia. Conclusions: This study provided fully comparable data on the occurrence and molecular characteristics of VIM-producing Enterobacteriaceae in a group of hospital units across Europe, documenting recent changes in their epidemiology.